Analisis Pengontrolan Water Treatment Bandara Djalaluddin Menggunakan Sistem Kerja Star Delta - Sianaga, Anastasya H.B.K; Hidayat, Jhoni; Fitriani, Ayu (Lembaga Yasin AlSys, 2024)
In knowing how efficient the use of the Star Delta circuit is, the need for a circuit on a 3 Phase motor and how to apply the circuit to a 3 Phase water pump motor. The research was conducted at Gorontalo Djalaluddin Airport which is located in Isimu Sel, Tolotio, Tibawa District, Gorontalo Regency, Gorontalo, Indonesia. The research was carried out using data collection methods. An example of the application of a star delta circuit to a water pump motor. An electric motor is included in the category of dynamic electric machines and is an electromagnetic device that converts electrical energy into mechanical energy. Electric motors in the industrial world are often referred to as the industrial